Corporation José R. Lindley: Balanced Scorecard implementation - Jáuregui Machuca, Kety Lourdes (2008)
José R. Lindley Corporation is one of the most important organizations that operates in the country with a prestigious tradition in the market of sodas trough its leader brand “Inca Kola”. This enterprise has as its main character keeping in the vanguard of the sector, demonstrating a high competitive level in the recent years. With the aim of keeping its leadership, facing successfully the diffi cult environment of the local market and entering international markets, José R. Lindley Corporation has constantly worried about incorporating management philosophies and tools that allow guaranteeing its sustainability in the time with a vision about the future. In this sense, it decided to implement a Balanced Scorecard (BSC), as a tool to measure and improve its productivity and effi ciency, in the framework of its corporative strategy. In other words, the BSC facilitated monitoring the degree of accuracy in the implementation of its strategy. In this context, the case illustrates how the process of the implementation of a BSC in José R. Lindley Corporation was performed, showing the complexity of the process that involved fi nancial resources and an important dedication of the organization, specially those ones who comes from the High Direction and the Information Systems Area to provide technological support. In addition, the case shows how it is possible to translate a strategy into a group of objectives and specifi c measures trough the BSC. Based on the cause-effect relation, it links the objectives with its respective indicators, strategic initiatives and corresponding plans of action.